Increased protein intake and meal frequency reduces abdominal fat during energy balance and energy deficit. (23rd May 2013) - Arciero, Paul J.; Ormsbee, Michael J.; Gentile, Christopher L.; Nindl, Bradley C.; Brestoff, Jonathan R.; Ruby, Maxwell
<x xml:space="preserve">Abstract</x> Objective Unrefined, complex carbohydrates and lean protein diets are used to combat obesity, although it's unknown whether more frequent meals may improve this response. The effects of consuming traditional (∼15%) versus higher (∼35%) protein intakes as three or six meals/day on abdominal fat, postprandial thermogenesis (TEM), and cardiometabolic biomarkers in overweight individuals during 28 days of energy balance (BAL) and deficit (NEG), respectively were compared. Design and Methods Overweight individuals (n = 30) were randomized into three groups: two high‐protein groups (35% of energy) consumed as three (HP3) or six (HP6) meals/day and one group consumed three meals/day of a traditional intake (TD3). Following a 5‐day baseline control (CON), subjects consumed their respective diets throughout a 56‐day intervention consisting of two, 28 day phases: a BAL followed by a NEG phase (75% of energy needs). Total body fat (BF) and abdominal BF (ABF), body weight (BW), TEM, and fasting biomarkers were assessed at the end of CON, BAL, and NEG phases. Results BW remained stable throughout CON and BAL in all groups, whereas BF (P < 0.001) and ABF (P < 0.01) decreased in HP groups and lean body mass (LBM) and leptin increased in HP6. Following NEG, BW decreased in all groups. BF, ABF, and leptin decreased in HP groups; LBM remained higher (P < 0.05), and TEM was highest in HP6 (P < 0.05). Conclusions Consuming increased protein (∼35%) more frequently (6×) throughout the day decreases BF and ABF, increases LBM and TEM, and favorably affects adipokines more than current recommendations for macronutrients consumed over three meals/day in overweight individuals during both BAL and NEG.